2007
DOI: 10.3136/fstr.13.20
|View full text |Cite
|
Sign up to set email alerts
|

Application of Supercritical CO2 Bubbling to Inactivate E. coli and Coliform Bacteria in Drinking Water

Abstract: The e#ect of the continuous flow of supercritical CO, microbubbles (the SC-CO, method) on the inactivation of both Escherichia coli in model water and coliform bacteria in water prior to treatment at a municipal water filtering plant were studied as a way to produce safe drinkable tap water. The number of surviving cells in both samples drastically decreased above a certain concentration of dissolved CO, (gῌ,/). When treated for +-.-min, cells were not detected at concentrations over gῌ-*. The dependences of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Electron micrographs of E. coli cells before and after SC-CO 2 treatment SEM photographs of E. coli cells before and after SC-CO 2 treatment are shown in Figure 4. In an earlier study we confirmed that surviving E. coli cells could not be detected after SC-CO 2 treatment (Kobayashi et al, 2007a). The damage in E. coli cells by SC-CO 2 treatment could not be observed by SEM.…”
Section: Results and Discussion Inactivation Of Microorganisms In Untsupporting
confidence: 64%
See 3 more Smart Citations
“…Electron micrographs of E. coli cells before and after SC-CO 2 treatment SEM photographs of E. coli cells before and after SC-CO 2 treatment are shown in Figure 4. In an earlier study we confirmed that surviving E. coli cells could not be detected after SC-CO 2 treatment (Kobayashi et al, 2007a). The damage in E. coli cells by SC-CO 2 treatment could not be observed by SEM.…”
Section: Results and Discussion Inactivation Of Microorganisms In Untsupporting
confidence: 64%
“…As described in our previous paper (Kobayashi et al, 2007a), water was taken from a municipal water filtering plant (Miyoshi, Hiroshima, Japan) prior to being treated for use as tap water. The coliform bacteria and total bacterial counts in this untreated water were approximately 4.0×10 2 MPN/100ml and 9.0×10 2 ~1.2×10 3 CFU/ml, respectively.…”
Section: Untreated Watermentioning
confidence: 99%
See 2 more Smart Citations
“…Far too little attention has been paid to water disinfection since the first study of Kobayashi et al (2007) have successfully carried out an attempt to transfer knowledge of HPCD from food disinfection to water disinfection. In recent years, there has been an increasing interest in applying HPCD to water treatment (Kobayashi et al, 2007(Kobayashi et al, , 2009a(Kobayashi et al, , 2009b(Kobayashi et al, , 2010Cheng et al, 2011) with the belief that pressurized CO 2 has all the advantages of conventional disinfection methods and overcomes their adverse effects to health. Questions have been raised as to why the major attention on HPCD has been paid to liquid media and water, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%